Storax, A Promising Botanical Medicine for Treating Cardio-Cerebrovascular Diseases: A Review - Xu, Zhuo; Lu, Danni; Yuan, Jianmei; Ren, Mihong; Ma, Rong; Xie, Qian; Li, Yong; Li, Jinxiu; Wang, Jian (Frontiers in Pharmacology, 2021)
In recent years, the incidence and mortality of cardio-cerebrovascular diseases have been increasing year by year, which has become global burden and challenge. Based on the holistic thinking of “brain disease affects the heart” and “heart disease affects the brain,” as well as the characteristics of multi-target and multi-path effects of Chinese medicine, Chinese medicine is more advantageous in the treatment of cardio-cerebrovascular diseases. As a botanical medicine, storax is known for its resuscitation, filth avoidance and pain-relieving effects in the treatment of cardio-cerebrovascular diseases. By reviewing and collating the relevant domestic and international literature in the past 10 years, we have sorted out an overview of the medicinal parts, traditional uses and chemical composition of storax. For the first time, based on the idea of “cerebral and cardiac simultaneous treatment,” the pharmacological activities and mechanisms of heart and brain protection of storax for treating cardio-cerebrovascular diseases were summarized and analyzed, showing that storax has the pharmacological effects of anti-cerebral ischemia, regulation of blood-brain barrier, bidirectional regulation of the central nervous system, anti-myocardial ischemia, anti-arrhythmia, anti-thrombosis and anti-platelet aggregation. It mainly exerts its protective effects on the brain and heart through mechanisms such as inhibition of inflammatory immune factors, anti-oxidative stress, anti-apoptosis, pro-neovascularization and regulation of NO release. On the basis of the current findings and limitations, the future research strategies and perspectives of storax are proposed, with a view to providing a reference for further application and development of this medicine, as well as contributing new thoughts and visions for the clinical application of “treating brain-heart synchronously”.